AB0008 Familial mediterranean fever (FMF) gene mutations (MEFV): are they a risk factor for coronary artery disease?. (23rd January 2014) - Kisacik, B.; Basar, N.; Ercan, S.; Pehlivan, Y.; Yilmaz, S.; Simsek, I.; Erdem, H.; Ozer, O.; Pay, S.; Dinc, A.; Onat, A.M.
Abstract : Background: Familial Mediterranean fever (FMF) is an autosomal recessive disease which predominantly affects certain ethnic groups mainly Sephardic Jews, Turks, Arabs and Armenians. The gene causing FMF, designated MEFV, encodes a protein called pyrin or marenostrin that is expressed mainly in myeloid bone marrow precursors, neutrophils, and monocytes. Objectives: Cardiovascular diseases (CVD) are very common in general population. The prevalence of coronary heart disease (CHD) is approximately one-third of total CVD. Atherosclerosis is responsible for main pathogenesis. Circulating inflammation markers may be correlated with atherosclerosis such as high-sensitivity C-reactive protein and homocysteine. Familial Mediterranean fever (FMF) is an autosomal recessive disease which predominantly affects certain ethnic groups mainly Sephardic Jews, Turks, Arabs and Armenians. The gene causing FMF, designated MEFV, encodes a protein called pyrin or marenostrin that is expressed mainly in myeloid bone marrow precursors, neutrophils, and monocytes. We herein aimed to determine the prevalence of MEFV mutations (all exon 2, 10 mutations) in early coronary heart disease (early CHD) and coronary heart disease (CHD) with multiple risk factors and healthy control population. Methods: The study population consists of three groups. Group 1 was consist of 91 patients with early CHD at <45 years of age for men, <40 years of age for women (male/female: 83/8), group 2 on the other hand included 106 patients with CHD at >50 years of age (male/female: 77/29) and finally in group 3, 119 healthy controls involved into study (male/female: 111/8). Results: None of patients was diagnosed with FMF. 38 patients (41.8%) with early CVD, 17 patients (16%) with CVD, 24 healthy control (20.2%) carried at least one mutated MEFV allele. Young patients with CHD have different risk factor profiles, clinical presentations, and prognoses than older patients. Young patients with CHD usually have multiple risk factors. Conclusions: This study suggests that MEFV mutations with early CHD patients had significantly increased in contrast to CHD patients and healthy controls. Disclosure of Interest: None Declared